High hydrostatic pressure extract of mulberry leaves ameliorates hypercholesterolemia via modulating hepatic microRNA-33 expression and AMPK activity in high cholesterol diet fed rats - Eunyoung Lee; Mak-Soon Lee; Eugene Chang; Chong-Tai Kim; Ae-Jin Choi; In-Hwan Kim; Yangha Kim (Food & Nutrition Research, 2021)
Background: Mulberry leaf (Morus alba L.) contains multiple bioactive ingredients and has been used in the treatment of obesity, diabetes, inflammation, and atherosclerosis. High hydrostatic pressure (HHP) processing has been developed for the extraction of bioactive compounds from plants. However, the hypocholesterolemic effect of the HHP extract from mulberry leaves and its underlying mechanism have never been investigated. Objective: The specific aim of the present study was to investigate the hypocholesterolemic property of a novel extract obtained from mulberry leaves under HHP in rats. Design: Sprague–Dawley rats were divided into four groups and fed either a normal diet (NOR), a high cholesterol diet containing 1% cholesterol and 0.5% cholic acid (HC), an HC diet containing 0.5% mulberry leaf extract (ML), or a 1% mulberry leaf extract (MH) for 4 weeks. Results: High hydrostatic pressure extract of mulberry leaves significantly reduced the HC-increased serum levels of triglyceride (TG), cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), and hepatic contents of TG and TC. The HHP extraction from mulberry leaves also increased the HC-decreased fecal TC and bile acid levels without changing body weight, food intake, liver weight, and serum activities of alanine transaminase (ALT) and aspartate transaminase (AST) (P < 0.05). The mulberry leaf extract significantly enhanced the expression of hepatic genes such as cholesterol 7 alpha-hydroxylase (CYP7A1), liver X receptor alpha (LXRα), and ATP-binding cassette transporters, ABCG5/ABCG8, involved in hepatic bile acid synthesis and cholesterol efflux (P < 0.05). In addition, the HHP extraction of mulberry leaves significantly suppressed hepatic microRNA(miR)-33 expression and increased adenosine monophosphate-activated protein kinase (AMPK) activity. Conclusion: These results suggest that the HHP extract of mulberry leaves lowers serum cholesterol levels by partially increasing hepatic bile acid synthesis and fecal cholesterol excretion through the modulation of miR-33 expression and AMPK activation in the liver.